The primacy of institutions reconsidered: The effects of malaria prevalence in the empirics of development - Kai Carstensen; Erich Gundlach (Kiel Institute for World Economics (IfW), 2005)
Some recent empirical studies deny any direct performance effects of measures of geography and conclude that institutions trump all other potential determinants of development. For given effects of institutional quality, our empirical results indicate quantitatively important direct negative performance effects of a measure of disease ecology, namely malaria prevalence. This finding appears to be robust to using alternative specifications, instrumentations, and samples. We conclude from our estimates that implementing good institutions appears to be necessary but not sufficient to generate a persistent process of successful economic development.
Keywords: O1; O4; 330; Economic development; institutions; malaria prevalence; instrument selection